Sanksi Pidana terhadap Pelaku Tindak Pidana Pembunuhan dengan Mutilasi dalam Hukum Pidana Indonesia - I Made Yasa Wahyuda; Anak Agung Sagung Laksmi Dewi; Diah Gayatri Sudibya (Fakultas Hukum, Universitas Warmadewa, 2022)
Murder by mutilation is a fairly heinous act where this murder is carried out by starting with the disappearance of a person's life then followed by the cutting of the victim's body from the head to the whole body. This was done to erase traces of murder. Mutilation when viewed in Indonesian criminal law is not clearly regulated so that in giving sentences to perpetrators it is also sometimes less stable, this results in concern and discomfort among the community if the perpetrator is not punished severely. Therefore, this research examines the regulation of the crime of murder by mutilation in Indonesian criminal law and analyses the criminal sanctions against perpetrators of the crime of murder by mutilation in Indonesian criminal law. The research method used is normative legal research using a statutory approach and a conceptual approach. The primary legal material of this research is sourced from regulations related to cases, the secondary legal material of this research is sourced from law books, legal journals. Data collection techniques using the method of quoting, summarizing and providing reviews. The results obtained from the formulation of the problem, namely the legal arrangements and sanctions imposed on perpetrators of murder by mutilation can be linked to articles 338 and 340 of the Criminal Code as well as examples of cases contained in the decision Number: 44/ PID.B/2014 /PN Srp Semarapura Klungkung